Improving saline-alkali soil and promoting wheat growth by co-applying potassium-solubilizing bacteria and cyanobacteria produced from brewery wastewater - Duan, Huijie; Liu, Wei; Zhou, Lixiu; Han, Bing; Huo, Shuhao; El-Sheekh, Mostafa; Dong, Haiwen; Li, Xiaomeng; Xu, Tongtong; Elshobary, Mostafa (Frontiers in Environmental Science, 2023)
Soil salinization is a serious ecological problem. Bacteria and cyanobacteria both have great potential for saline-alkali soil improvement. However, the effect of co-applying bacteria and cyanobacteria on soil improvement and crop growth promotion in saline-alkali soil remains unclear. In this study, the effects of Paenibacillus sabinae (potassium-solubilizing bacteria) and Leptolyngbya sp. RBD05 (cyanobacteria), produced in brewery wastewater, on soil properties, wheat growth, and wheat stress tolerance were studied by applying them to saline-alkali soil alone or in combination. The study indicated that Paenibacillus sabinae and Leptolyngbya sp. RBD05 have important roles in increasing wheat growth, N:P ratio, K:Na ratio, proline content, and superoxide dismutase activity, as well as in slowing the decline of soil nutrient content caused by wheat absorption. Compared to the control group, the co-application had the best effect on soil available K content, wheat dry weight, and wheat root length (increased by 26%, 85%, and 70%, respectively); and it was more conducive to promoting the wheat K:Na ratio (increased by 41%), which would better improve the wheat’s saline-alkali stress tolerance. This study provided a new and clean strategy to improve saline-alkali soil quality and promote crop growth by the bacteria and cyanobacteria produced from wastewater treatment.